Energy-Saving Labels, Social Media, and the Sequential Mediation of Curiosity and Attitude in Energy-Efficient Household Appliance Adoption - Andika; Maslikhah; Tampubolon, Nobel Kristian Tripandoyo; Anisah, Tiara Nur; Joshi, Mahesh Chandra (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2025)
Objective: This study examines the impact of energy-saving labels and social media on consumers' intentions to purchase energy-efficient household appliances (EHAs), utilizing the Stimulus-Organism-Response (S-O-R) framework with curiosity and attitude as sequential mediators. Design/Methods/Approach: Data were collected through an online consumer survey, which resulted in 318 valid responses. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to test the hypothesized relationships. Findings: The results indicate that energy-saving labels and social media significantly enhance consumer curiosity about EHAs, strengthening positive attitudes and purchase intentions. Curiosity and attitude sequentially mediate the effects of these external stimuli on purchase intention, with energy-saving labels exerting a more decisive influence than social media across the mediation pathway. Originality/Value: By extending the S-O-R framework to EHA adoption in a developing economy context, this study offers new insights into the psychological mechanisms shaping sustainable consumption, particularly the sequential mediation through curiosity and attitude. Practical/Policy implications: The findings suggest that clear energy-saving labels and culturally relevant social media campaigns can stimulate consumer curiosity and foster positive attitudes. These strategies can inform marketing practices and policy initiatives to accelerate EHA adoption and contribute to broader global sustainability goals.